Potencial prebiótico da farinha do subproduto de umbu-cajá (Spondias spp.) na microbiota colônica humana - Oliveira, Jordana Nunes de (2023)
Umbu-cajá (Spondias spp.) is a tropical fruit typical of Northeastern Brazil, considered a natural hybrid between the umbuzeiro (Spondias tuberosa) and the cajazeira (Spondias lutea). The byproduct from the industrial processing of umbu-cajá has high nutritional value, due to the amount of dietary fiber and bioactive compounds, which together may have prebiotic potential. Furthermore, the use of the umbu-cajá by-product can prolong the use of its fruits in periods outside the harvest, contributing to the sustainability of the food system. In this context, the study aimed to develop a flour from the by-product of agro-industrial processing of umbu-cajá (FUC) and evaluate the potential prebiotic effect during in vitro colonic fermentation. The flour was made from the by-product of umbu-cajá, followed by physical-chemical characterization. Subsequently, the flour was subjected to in vitro gastrointestinal digestion, and the relative abundance of bacterial groups present in the human colonic microbiota was evaluated using the in situ hybridization fluorescence technique coupled with multiparametric flow cytometry during 48 h of in vitro fermentation, determining prebiotic indices. Microbial metabolic activity was evaluated by determining pH, quantifying sugars, organic acids, identifying the metabolic profile and antioxidant activity, evaluated at times 0, 24 and 48 h of colonic fermentation. The results were expressed as the mean ± estimated standard deviation and subjected to analysis of variance (ANOVA) followed by the Tukey test; and unpaired Student's t test. P values <0.5 were considered significant (5% significance level). Umbu-cajá flour had low moisture content, high insoluble fiber content (57.46 ± 0.28 mg/100 g) and flavonols Quercetin 3-Glucoside and procyanidin B2 (36.96 ± 0.31 and 9.81 ± 0.02 mg/100 g, respectively). Digested FUC showed a positive prebiotic index (5.37 ± 1.16 to 11.86 ± 1.47) and intense microbial metabolic activity during colonic fermentation, from the consumption of sugars (glucose and fructose), production of short-chain fatty acids (acetic, lactic, butyric and propionic) proven from the global metabolic profile, concomitant with a decrease in pH values and an increase in antioxidant activity. These findings show that FUC is a potentially prebiotic product, due to its ability to positively modulate the intestinal microbiota. These results may encourage the agro-industrial sector to evaluate fruit processing by-products as value-added products.